Factors Affecting Waqif’s Decision in Selecting Productive Waqf (Case Study at Dompet Dhuafa Republika) - Nurlaila Mahdiah; Neneng Hasanah; Tita Nursyamsiah (Department of Islamic Economics, IPB University, 2019)
Indonesia as a country with largest Muslim population in the world has potentials in utilizing its Islamic philanthropy source of funds to alleviate social and economic problems in society, one is through waqf. Waqf that is managed productively has proven its positive contribution to the advancement of a country. However, the collecting of waqf fund is still dominated by direct waqf (non-productive) based on the instruction a waqif gave. This shows that the majority of waqif prefers direct waqf (non-productive) to productive one. Therefore, the purpose of this study is to analyze the factors that affect waqif’s decision in selecting productive waqf. Data collection is done by the questionnaires given to the respondents. The respondents are 65 waqif at Dompet Dhuafa Republika. The method used in this study is descriptive analysis and logit regression. The result shows that waqif’s decision in selecting productive waqf is affected by their comprehension on productive waqf, age, subjective norm, and marital status.